Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
7/13 x 7/15 - 5/12 x 7/13 + 7/13 x 8/15 =7/13x(7/15-5/12+8/15)=7/13x7/12=49/156
12/13×8/15×7/9=........................
........................
a) x - (-7) = -8 + (-2)
x + 7 = -8 - 2
x + 7 = -10
x = -10 - 7
x = -17
b) x + (12 - 15) = /-3/ - 7
x + (-3) = 3 - 7
x - 3 = -4
x = -4 + 3
x = -1
c) (12 - x) - (-10) = -25
(12 - x) + 10 = -25
12 - x = -25 - 10
12 - x = -35
x = 12 - (-35)
x = 12 + 35 = 47
d) (-20) - (15 - x) = -50
15 - x = -20 - (-50)
15 - x = -20 + 50
15 - x = -30
x = 15 - (-30)
x = 15 + 30
x = 45
1) 3x - 6= 5x + 2
5x - 3x = -6 - 2
2x = -8
x = -4
2) 15 - x = 4x - 5
4x + x = 15 + 5
5x = 20
x = 4
Tương tự như trên
6) 8(x – |-7|) – 6(x – 2) = |-8|.6 – 50
7) -7(5 – x) – 2(x – 10) = 15
8) 4(x – 1) – 3(x – 2) = -|-5|
a) \(\frac{7}{12}+\frac{x}{15}=\frac{1}{20}\)
=> \(\frac{35}{60}+\frac{4x}{60}=\frac{3}{60}\)
=> 35 + 4x = 3
=> 4x = -32
=> x = -8
b) \(\frac{-7}{x}+\frac{8}{15}=\frac{-1}{20}\)(ĐK \(x\ne0\))
=> \(\frac{-7}{x}=\frac{-1}{20}-\frac{8}{15}\)
=> \(\frac{-7}{x}=\frac{-3}{60}-\frac{32}{60}\)
=> \(\frac{-7}{x}=\frac{-35}{60}\)
=> \(\frac{-7}{x}=\frac{-7}{12}\)
=> x = 12(TM)
15 + x = 15
x = 15 -15
x = 0
15+x=7-(-8)
15+x=7+8
15+x=15
x=15-15
x=0
vậy x=0